Insights Into Microbially Induced Salt Tolerance and Endurance Mechanisms (STEM) in Plants - Kaushal, Manoj (Frontiers in Microbiology, 2020)
Salt stress threatens the achievement of sustainable global food security goals by inducing secondary stresses, such as osmotic, ionic, and oxidative stress, that are detrimental to plant growth and productivity. Various studies have reported the beneficial roles of microbes to ameliorate salt stress in plants. This review emphasizes salt tolerance and endurance mechanisms (STEM) in microbial inoculated (MI) plants, which ensure plant growth and survival. Well established STEM have been documented in MI plants and include conglomeration of osmolytes, antioxidant barricading, recuperating nutritional status, and ionic homeostasis. This is achieved via involvement of P solubilization, siderophore production, nitrogen fixation, selective ion absorption, volatile organic compound (VOC) production, exopolysaccharide (EPS) production, modifications to plant physiological processes (photosynthesis, transpiration and stomatal conductance), and molecular alterations to alter various biochemical and physiological processes. STEM in MI plants ensures plant growth by improving nutrient uptake and maintaining ionic homeostasis, promoting superior water use efficiency and osmoprotection, enhancing photosynthetic efficiency, preserving cell ultrastructure, and reinforcing antioxidant metabolism. Molecular research in MI plants under salt stress conditions has found variations in the expression profiles of genes such as HKT1, NHX, and SOS1 (ion transporters), PIPs and TIPs (aquaporins), RBCS, RBCL (RuBisCo subunits), Lipoxygenase2 (jasmonic acid (JA) signaling), ABA (abscisic acid)-responsive gene, and APX, CAT, and POD (involved in antioxidant defense). Proteomic analysis in arbuscular mycorrhizal fungi (AMF) inoculated (AI) plants revealed upregulated expression of signal transduction proteins, including Ca2+ transporter ATPase (PMCA), calcium-dependent protein kinase (CDPKs), calmodulin (CaM), and energy-related proteins (NADH dehydrogenase, iron sulfur protein NADH dehydrogenase, cytochrome C oxidase, and ATP synthase). Future research should focus on the role of stress hormones, such as JA, salicylic acid (SA), and brassinosteroids, in salt stressed MI plants and how MI affects the cell wall, secondary metabolism, and signal transduction in host plants.